Дидактички аспекти за развој на едукативни содржини со користење на ИКТ - Василева, Марина (ФИНКИ, УКИМ, Скопје, 2017)
In this thesis we describe the role of learning based on traditional children's games in the teaching process, the role of ICT in "playing and learning" as well as the benefits of communication student - student, teacher-student, parent, student, teacher - mentor. The aim of the doctoral dissertation is to make a detailed analysis of the changes occurring in the learning process based on traditional kids games and to discover didactic aspects in the implementation of ICT in teaching as a model of integrative material approach that should be correlated with the entire teaching process. While perceived opportunities for digitization of cultural heritage through the creation of digital educational content. The research is aimed at reviving forgotten traditional children's games and pedagogical systematic planning for their implementation into the teaching process by using ICT. We analyzed the adapted curricula in science and mathematics, according to Cambridge program with a display of thematic areas in which it can realize educational goals with concrete playing activities. We developed a model of an instructional manual for teachers with preparations for the use of technology in and out of the classroom and developed a simulator model of programmed Kinect game (Zavor) with pedagogical concept to implementation. Broad is the spectrum of effects of learning based on traditional kids games. They encourage fun, visibly greater motivation for new knowledge, affect thought processes affect the physical development and represent an attractive way to transform the teaching process with high performance, innovative and creative learning environments according to curricula. The study is based on the educational project "Grandma's Games" which revived processed twelve traditional children's games, implemented in accordance with didactic principles and rules instruction in six major urban and rural school environments in the country. 175 students from different ethnic backgrounds were involved, and the games were implemented in the curriculum, the implementation of interdisciplinary and educational purposes multidisciplinary subjects as mathematics, natural sciences, arts, social sciences and languages. In order to evaluate the impact of traditional games, a survey was conducted among 177 teachers and 37 parents of students. Descriptive method collected data from a sample of respondents to assess their views and opinions regarding the application of model-based learning traditional games as a form of research, found a frequency of use of ICT in teaching teachers and evaluated a model programmed Kinect game (Zavor). The results were used to make conclusions about the educational aspects that are most represented. These elements are the pillars on which we base our recommendations. Traditional children's games and the latest technology can be digitized as part of world cultural heritage with programming learning activities, according didactic rules and principles, including elements of the physical movement of the entire musculature of students as an effective model for learning in these modern technological times.
Didactic Aspects for Development of Eductional Content Using ICT
Докторска дисертација одбранета во 2017 година на Факултетот за информатички науки и компјутерско инженерство во Скопје, под менторство на проф. д–р Владимир Трајковиќ.
Keywords: game-based learning, students’ experience, traditional children's games, digitalization, ICT, primary education